Monomaniac revenge in Melville’s “Moby Dick” and Bronte’s “Wuthering Heights” - Salih, Ismail Khalaf; AbdulKareem, Danear Jabbar; Abdullah, Omar Najem (Penerbit Universiti Kebangsaan Malaysia, 2021)
Revenge can be one of consequences of bad feeling towards others. This feeling of anger, hatred and prejudice could be based on traumatic visible or invisible experience. The level of that anger and hatred depends on the volume of damage caused by the action or judgment and, on other hand, it depends on man’s endurance and tolerance upon that action or judgment. Revenge can be individual or collective as well. Individually, it is driven personally as a reaction of other’s perceived harm when the individual desire is set to retaliate for bringing justice and satisfying his need. Collectively, most of ancient wars and conflicts were based on the concept of revenge which mostly brought collective devastation. This study will utilize rereading of the canonical texts; Moby Dick” by Herman Melville and “Wuthering Heights” by Emily Bronte, to make better understanding of the ‘monomaniac revenge’ by highlighting and analyzing the main characters in the two novels above ‘Ahab’ and ‘Heathcliff’, respectively, and their destructive revenge under the light of Psychological theory. Ahab was isolated from his family. Heathcliff was dismissed by his family. Later on they both lost their lives. Melville and Bronte prove that destructive revenge brings destructive results. The top focus of the study analysis will be on how Ahab and Heathcliff’s excessive desire of revenge develops and then brings them and people around to death.